Penerapan Analisis Sistem dalam Konservasi Tanah dan Air - Darmadi Darmadji (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
Study on soil and water conservation engineering can be approached easily by applying analysis system approach. This application will lead to the understanding that problems emerge in the system are strongly influenced by several factors, both dependent factors such as human factor, vegetative etc. and free factors such as climate. So, it is also understood that applying several disicpline of science can also approach problems solving in soil and water conservation in the certain area. Analysis system also help management process in implementing soil and water conservation activities in terms of solid and better managements works started from planning, implementation and the last monitoring and evaluation stage. Considering to all of these than it is suggested that system approached and system analysis should be introduced to students who study soil and water conservation courses in the higher education.